A case of Caroli's disease complicated with recurrent hepatic encephalopathy due to portal-systemic shunts - MIZUNO, Koichi; MITAMURA, Keiji; HIGUCHI, Kenichi; FUJIMURA, Kenji (Kanzo, 1994)
A 63-year-old man who had his histories of disturbances of consciousness was admitted to our hospital with complaints of depression of consciousness level. The diagnosis of hepatic encephalopathy was made from his clinical course, abnormal liver function tests, elevation of serum ammonia and abnormal E.E.G. findings. Cholangiography showed the multiple cystic dilations of the intrahepatic biliary tract without dilatation of the extrahepatic bile ducts. These findings are compatible with the main characteristics of Caroli's disease. Angiography showed shunt formation from superior mesenteric vein to inferior vena cava. Histological findigns of the liver revealed the dilatation and the proliferation of intrahepatic biliary tract, mild fibrosis of periductal area and proliferation of fibrous tissue of the portal area. But no pseudolobular formation was observed. A case of Caroli's disease associated with periportal fibrosis and accompanied by portal-systemic shunts is rare. Compression of portal vein due to dilatation of intrahepatic biliary tract or congenital extrahepatic portal-systemic shunt could be considered as a cause of shunting in this case.